ANALISIS GREEN ACCOUNTING, TINGKAT UTANG, DAN SUSTAINABLE GROWTH TERHADAP KUALITAS LABA DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MODERASI - Zahwa Bilqis Zarakhan Ifo; Nera Marinda Machdar (Jurnal Ilmiah Akuntansi, 2026)
Earnings quality is an important indicator for assessing corporate performance and sustainability. This literature review aims to analyze the influence of green accounting, leverage, and sustainable growth on earnings quality, with earnings management as a moderating variable. The method used is a systematic review of selected national and international journal articles from the 2019–2025 period. The results of the literature synthesis indicate that green accounting and sustainable growth positively affect earnings quality through increased transparency and financial stability. Conversely, high leverage negatively impacts earnings quality as it encourages earnings management practices. Furthermore, earnings management plays a role in weakening the positive influence of green accounting and sustainable growth, while strengthening the negative impact of leverage. This study concludes that commitment to sustainability, a healthy funding structure, and control of earnings management are key factors in improving a company's earnings quality.